Christians, Jews, and Magic in the Sasanian Realm: Between Confrontation and Cooperation - Minov, Sergey (Entangled Religions, 2022)
This essay focuses on one particular aspect of Jewish-Christian relations during the Sasanian period, namely various types of interaction between the two religious groups in the domain of magic. For that purpose, two distinctive bodies of textual evidence are examined: hagiographical literature produced by Syriac Christians, and Aramaic magic bowls, Jewish as well as Christian. Illuminating and complementing each other, the two corpora shed light on the dual dynamics of competition and cooperation between Jews and Christians in the field of popular religion.